SELEKSI DAN PENGUKURAN KANDIDAT POHON PLUS GAHARU (Aquilaria malaccensis) DI DESA KRAWANG SARI KECAMATAN NATAR - Rila Pangesti; Afif Bintoro; Duryat Duryat (Fakultas Kehutanan Universitas Jambi, 2020)
Plus trees are trees that can produce high quality seeds. To get a plus tree, it is necessary to select and measure the candidate tree. Plus trees selection can be done by applying gradual screening based on agarwood plus trees criteria. The criteria for agarwood plus trees are that the tree has not been inoculated, the tree has produced fruit, the condition of the tree is healthy, the tree is tall, the tree has a large diameter and the tree has a large number of branches. The results showed that there were 5 trees that qualified as a plus tree including trees number 275, 153, 195, 243 and 321. The most superior plus tree was tree plus number 275 which had a height of 7.2 meters, a diameter of 135 cm and had 18 branch.